Safyre. A new concept for adjustable minimally invasive sling for female urinary stress incontinence [Safyre. Un nuevo concepto de cabestrillo ajustable mínimamente invasivo para la incontinencia urinaria por estrés femenina] - Palma, P.C.R. (2004)
Introducción: SAFYRE is a new readjustable and minimally invasive sling for the treatment of stress urinary incontinence (SUI). Attempts to restore the normal suburethral hammock using an anatomical approach have been made in.recent years. The authors report their experience with this device, which associates the efficacy of slings with readjustability. Material and Methods: A total of 100 consecutive patients with clinical and urodynamic diagnosis of SUI underwent SAFYRE sling procedure. The age range was from 40 to 71 mean age 63 years. Seventy-five patients (75%) presented previous failed anti-incontinence procedures. Physical clinical examination, stress test, pad use and a urodynamic study were performed before the surgery. All the patients presented symptoms of SUI and 30 % also reported mild urgency. Results: The average follow up period was 14 months (12 - 30 months). The mean operative time was of 25 minutes. Dystopia repair was performed whenever necessary, during the same procedure. The average hospital stay was 24 hours. In 3% of the implants, bladder perforation occurred. During the postoperative period, 26 patients developed urgency symptoms. During that follow up period. 92% were found to be continent, 3% reported an improvement and 5% were dissatisfied. Conclusion: SAFYRE is a safe and quick procedure that allows for postoperative readjustment. This technique may be an attractive alternative if the good result obtained so far proves to be long lasting.